The Effects Of Zinc Oxide Microstructure On The Electrical Characteristics Of Low-Voltage Ceramic Varistors. [TK7871.99.V3S525frb] [Microfiche 7646] - Ahmad, Shahrom (2004)
The effects of ZnO microstructure, on the electrical characteristics of low-voltage ceramic varistors, have been investigated in this work.